Association between Knowledge, Attitude, and Practice on Dietary Fiber Intake and Body Mass Index among Undergraduate Students in Universiti Kebangsaan Malaysia - Mat Ludin, Arimi Fitri; Ismail, Munirah; Othman, Mohd Sham; Vanoh, Divya; Huoy Tyng, Chai; Ibrahim, Irdina; Surang, Jasmine Lavang; Jayiddin, Muhammad Adam; Ibrahim, Noor Afiifah; Abdullah, Nur Arina Shazrina; Harun, Nur Athirah; Rashidi, Nur Fatihah; Chen, Lew Leong (Makara Journal of Health Research, 2024)
Background: A fiber-rich diet lowers the risk of various diseases by increasing fecal bulk, shortening intestinal transit time, and stimulating intestinal flora. This study examines the association between knowledge, attitude, and practice (KAP) regarding dietary fiber intake and body mass index (BMI) among Dentistry and Software Engineering undergraduates. Methods: This cross-sectional study included 95 Dentistry and 92 Software Engineering students at the Universiti Kebangsaan Malaysia. The KAP questionnaire was analyzed for its reliability using Cronbach’s alpha and distributed through email. Results: Most respondents had normal weight. The Software Engineering students had a higher percentage of overweight and obese individuals than the Dentistry students. KAP measurements for both groups were moderate across all variables. No differences were found in attitude and practice levels between both groups. However, the Software Engineering students had higher knowledge of dietary fiber intake. KAP did not influence BMI in both groups. Factor analysis showed a high association between KAP on dietary fiber intake and BMI status among Software Engineering students compared to dentistry students. Conclusions: The level of KAP on dietary fiber intake is associated with BMI status among undergraduate students.